Perceptions of students in the Malay language program at Feng Chia University - Chou, Cindy Huey-Nah (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2021)
Identifiable motives and strong perseverance are crucial factors for Effective Foreign Language Acquisition. There is no doubt that motivation for learning English for instrumental reasons is strong since English as a lingua franca is globally required of education advancement and career development. Likewise, learning Japanese and Spanish is also considered as important for Taiwanese students to enhance competitiveness in the global job market as Taiwanese corporates are reaching out to all continents of the world. But the exact reasons why an increasing number of Taiwanese students are learning Malay language still remain unclear. The fact that Malay language is the most used language in ASEAN and thus possesses the strongest demand by global industries investing in the Malay world. Reasonably, it should play a determining role in attracting more Taiwanese learners of Malay language. However, whether Taiwanese students identify the growing global demand of Malay language and whether they recognize the potential importance of understanding Malay language and culture in their future endeavors still need to be explored. Program planners and educators would not be able to deliver lessons that meet the needs of students without a solid understanding of students’ expectations of the efficacy of Malay language courses. Therefore, this study aims to gain a deeper understanding of the experiences of studying the Malay language of Taiwanese students at Feng Chia University. This study, in particular, is conducted to unveil reasons and outcomes of learning Malay language and trends.